2009
DOI: 10.1007/s00125-009-1375-y
|View full text |Cite
|
Sign up to set email alerts
|

Variants in KCNQ1 are associated with susceptibility to type 2 diabetes in the population of mainland China

Abstract: Aims/hypothesis Two recent genome-wide association studies have identified several novel type 2 diabetes susceptibility variants in intron 15 of the KCNQ1 gene. We aimed to evaluate the effects of the variants in KCNQ1 on type 2 diabetes and metabolic traits in the population of mainland China. Methods Three candidate single nucleotide polymorphisms were genotyped in 1,912 individuals with type 2 diabetes and 2,041 normal controls using the ligase detection reaction method.Results We confirmed the association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
3
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 27 publications
4
65
3
1
Order By: Relevance
“…It is worth noting that there was a disparity between patients with type 2 diabetes and controls with respect to the effect of KCNQ1 on obesity in the study, which is distinct from a previous study which showed an association of KCNQ1 with BMI in control individuals in the same direction as that observed in our diabetic patients [7].…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…It is worth noting that there was a disparity between patients with type 2 diabetes and controls with respect to the effect of KCNQ1 on obesity in the study, which is distinct from a previous study which showed an association of KCNQ1 with BMI in control individuals in the same direction as that observed in our diabetic patients [7].…”
Section: Discussioncontrasting
confidence: 98%
“…KCNQ1 has shown the strongest association with type 2 diabetes in East Asians, possibly through its effect on beta cell function [4][5][6]. It has also been linked to BMI in Han Chinese control individuals [7]. However, whether it is associated with obesity is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Our results were in agreement with those reported by Pecioska et al 21 The T allele of rs2237892 in the KCNQ1 gene was reported to be associated with increased waist circumference (P¼0.043). 24 However, the subjects with T allele had lower VFA in our study. A lack of association of type 2 diabetes loci, and VFA and SFA may be due to the low power of this study.…”
Section: Discussioncontrasting
confidence: 64%
“…[20][21][22] However, there are few reports of the association between type 2 diabetes susceptibility SNPs and visceral fat accumulation. 21,23,24 Associations between type 2 diabetes susceptibility SNPs, except those exited in the FTO gene and visceral fat mass determined by using more precise method, such as CT and magnetic resonance imaging, have not been elucidated yet. Therefore, we investigated the association between type 2 diabetes susceptibility SNPs and fat distribution (VFA and SFA) as determined by CT.…”
Section: Introductionmentioning
confidence: 99%
“…This meta-analysis about rs2237892 polymorphism and T2DM involve 40 article [2,[35][36][37][38][39][40][42][43][44][45][46], contain 52 study data set, 61757 T2DM patient and 59078 control(only calculate once in every study`s case and control group). The association of rs2237892 polymorphism and rising T2DM incident risk proved former study result [2,4,[7][8][9][11][12][13][14][15][16][17][21][22][23][24]27,[29][30][31]36,[39][40][41][42][43][44][45][46].…”
Section: Main Discoversmentioning
confidence: 99%